2019
DOI: 10.1590/1413-81232018242.34572016
|View full text |Cite
|
Sign up to set email alerts
|

Hábitos alimentares de adolescentes quilombolas e não quilombolas da zona rural do semiárido baiano, Brasil

Abstract: Resumo O objetivo deste artigo é descrever o consumo e o comportamento alimentar de adolescentes quilombolas e não quilombolas da zona rural do sudoeste baiano. Estudo transversal com 390 adolescentes de 10 a 19 anos em 2015, utilizando questionário adaptado da PeNSE e PNS. O consumo alimentar foi avaliado pela frequência nos últimos 7 dias de alimentos marcadores de alimentação saudável e não saudável. Realizar o desjejum foi marcador de comportamento saudável e, realizar refeição enquanto assistia TV, de não… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
(29 reference statements)
1
2
0
4
Order By: Relevance
“…According to Sousa et al ( 16 ), adolescents from the same rural regions investigated in the present study presented healthier food intake and diet than urban adolescents. The quilombola adolescents had a high intake of beans but a low intake of more expensive foods, like milk, vegetables, and fruits, which correlate with the higher vulnerability of these communities by impacting their access to a healthier and more varied diet ( 16 ).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…According to Sousa et al ( 16 ), adolescents from the same rural regions investigated in the present study presented healthier food intake and diet than urban adolescents. The quilombola adolescents had a high intake of beans but a low intake of more expensive foods, like milk, vegetables, and fruits, which correlate with the higher vulnerability of these communities by impacting their access to a healthier and more varied diet ( 16 ).…”
Section: Discussionsupporting
confidence: 55%
“…A study carried out in the Northeast of Brazil showed differences in the intake of healthy food between quilombola and non-quilombola rural adolescents. Quilombola adolescents had a lower intake of milk, vegetables, and fruits when compared to the non-quilombola adolescents ( 16 ), which may adversely impact the weight of this population.…”
Section: Introductionmentioning
confidence: 95%
“…De acordo com Sousa et al (2019), a adolescência é um período da vida caracterizado por estímulos de persuasão à hábitos e comportamentos, deixando esse público vulnerável no ato de suas escolhas. Os maus hábitos obtidos nesta fase podem influenciar o comportamento alimentar ao longo da vida, refletindo fatores de risco para o desenvolvimento de doenças crônicas não transmissíveis e traumas psicológicos.…”
Section: Adolescentes E Seus Hábitos Alimentaresunclassified
“…Entretanto, o paradoxo nutricional proposto há mais de 15 anos nos Estados Unidos evidencia também a associação entre IA e excesso de peso (Dietz 1995;Kursmark & Weitzman 2009). Embora determinados estudos apontem um estado de insegurança alimentar envolvendo populações quilombolas (Cordeiro et al 2014;Sousa et al 2019;E. Silva et al 2017), ainda há lacunas do conhecimento a serem compreendidas.…”
Section: Introductionunclassified